Coastal resource assessment for surf tourism in tourism in Thailand - Steven Andrew Martin (Prince of Songkla University Faculty of Service Industries (Hospitality and Tourism Management International Program), 2013)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2010